اسهامات العلماء والمفكرين في أرخبيل ملايو في تطور المجتمعات ونشر التعاليم اﻹسلامية = Ishamat al-ulama' wa-al-mufakkirin fi arkhabil Malayu fi tatawur al-mujtama'at wa-nasr al-ta'alim al-Islamiyah - Ahmad H.Osman, Rahmah; Zubir, Badri Najib; Chik, Abdul Rahman; Ali, Asem Shehadeh Saleh (International University of Africa, Sudan, 2014)
This study will confine to thirty scholars who constituted the core of scholarly networks in the Malay Archipelago. These scholars are selected from diverse backgrounds and different eras in the history of the Malay Archipelago. In spite of the above diversity, all these scholars have two things in common. Firstly, they all originated from the Malay Archipelago and secondly they shared the passionate interest to develop their respective communities. Therefore, it is only appropriate that this study focuses on the contributions of these scholars in the development and enhancement of their communities in the Malay Archipelago through means of religious propagation and Islamic teachings during the time.